KARAKTER SPESIFIK EKSTRAK DAUN YODIUM (Jatropha multifida L.) DARI TIGA LOKASI TEMPAT TUMBUH DI JAWA TIMUR - Dyah Aryantini; Erni Anika Sari; Dani Nanda S.W (Prodi Farmasi Fakultas Kedokteran Universitas Hang Tuah, 2021)
Jatropha multifida L. is a plant that has many medicinal properties. The active compounds of this plant include tannins, saponins, flavonoids, and phenols. However, the content of active compounds and the quality of extracts of a medicinal plant cannot be guaranteed to be in the same amount, and this is due to the influence of different growing sites. Therefore it is essential to do standardization. This study aims to characterize iodine leaf extracts from the cities of Kediri, Nganjuk, and Madiun. Specific parameter tests include the section's identity, organoleptic, content of soluble compounds in water and ethanol 96%, and screening for phytochemical flavonoids, tannin alkaloids, and saponins. This study can be concluded that extracts from Kediri, Nganjuk, and Madiun have a thick extract form with a blackish-brown color and have a distinctive odor and bitter taste. Based on phytochemical screening, all extracts contain alkaloids, flavonoids, tannins, saponins. Furthermore, the test levels of soluble compounds in ethanol 96% from Kediri, Nganjuk, and Madiun were 74; 77.70; 73.52%, and the class of soluble compounds in water were 40.90; 31,78, 41.87%.